Senior managers’ perceptions of executive development in the Eastern Cape department of education - Mtebele, Nozibele (My University, 2022)
Organisations participate in executive development to improve the capabilities of senior managers to be more proficient in performing their responsibilities. This study examined the perceptions of senior managers in the Eastern Cape Department of Education in South Africa on the Executive Development Programme (EDP) they had participated in. This research is a qualitative, descriptive case study utilising semi-structured interviews to collect primary data from four categories of participants which included senior managers, their supervisors, programme coordinators and facilitators. Secondary data was also collected from the department’s official documents. The findings of the study revealed that participants perceived the EDP as beneficial in as far as capacitating senior managers in their executive roles. The findings further provided the department deeper insight on how the EDP can enrich capacity development of senior managers and ultimately impacting the achievement of positive education outcomes in the department.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in 50% requirement for the degree of Master of Management (in the field of Public and Development Sector Monitoring and Evaluation)